2018
DOI: 10.1002/jia2.25043
|View full text |Cite
|
Sign up to set email alerts
|

Conditional cash transfers and the reduction in partner violence for young women: an investigation of causal pathways using evidence from a randomized experiment in South Africa (HPTN 068)

Abstract: IntroductionEvidence has shown that the experience of violence by a partner has important influences on women's risk of HIV acquisition. Using a randomized experiment in northeast South Africa, we found that a conditional cash transfer (CCT) targeted to poor girls in high school reduced the risk of physical intimate partner violence (IPV) in the past 12 months by 34%. The purpose of this analysis is to understand the pathways through which the CCT affects IPV.MethodsHPTN 068 was a phase 3, randomized controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
53
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 38 publications
2
53
0
4
Order By: Relevance
“…a. Gender-based targeting: One of the most prevalent gender-aware design features is the targeting of transfers or benefits to women, rather than to men or to households. Some programs specifically target women (girls) as primary caregivers of young children, or do so to meet program objectives related to maternity benefits (Grépin, Habyarimana, and Jack 2019;Cohen et al 2017), or widow pension programs, or those aimed at specifically benefiting adolescent girls (Baird, De Hoop, and Özler 2013;Kilburn, Pettifor, et al 2018). While putting benefits in the hands of women (girls) may enhance pre-conditions for favorable impacts, simply reaching women (girls) does not equal benefiting women (girls) for transformative outcomes.…”
Section: Ssns In Africa: the Role Of Gender In Program Designmentioning
confidence: 99%
“…a. Gender-based targeting: One of the most prevalent gender-aware design features is the targeting of transfers or benefits to women, rather than to men or to households. Some programs specifically target women (girls) as primary caregivers of young children, or do so to meet program objectives related to maternity benefits (Grépin, Habyarimana, and Jack 2019;Cohen et al 2017), or widow pension programs, or those aimed at specifically benefiting adolescent girls (Baird, De Hoop, and Özler 2013;Kilburn, Pettifor, et al 2018). While putting benefits in the hands of women (girls) may enhance pre-conditions for favorable impacts, simply reaching women (girls) does not equal benefiting women (girls) for transformative outcomes.…”
Section: Ssns In Africa: the Role Of Gender In Program Designmentioning
confidence: 99%
“…Only three studies measured both primary and secondary outcomes [30,38,43]. Primary outcome measures included unwanted sexual touching [35], forced sex [30,32,33,36,37,41,[44][45][46] and rape perpetration [30, 34,36], sexual assault (forced sex and/or touching) [47], any physical or sexual IPV exposure [30,34,37,42] and perpetration [30,32,34,37,38], physical IPV exposure [32,33] and perpetration [32], and emotional IPV exposure and perpetration [32]. Secondary outcome measures included gender-equitable attitudes [30,38,40,43,48], attitudes towards coerced sex [39] and acceptance of IPV [40].…”
Section: Intervention Outcomesmentioning
confidence: 99%
“…Evidence has also shown that CT programmes can reduce violence by alleviating day-to-day stress and conflict among couples, enhancing the psychosocial well-being of household members and the confidence and decision-making abilities of the women in those households [ 14 ]. A sub-study conducted recently among AGYW participating in HPTN 068, showed that conditional cash transfers (CCT) delayed coital debut and reducing the recipients’ number of sexual partners thereby giving them greater agency over partner choice [ 15 ].…”
Section: Introductionmentioning
confidence: 99%